PREFERENSI NYAMUK AEDES AEGYPTI PADA BEBERAPA MEDIA AIR - Wuwungan, Antje A; Lumanauw, Saartje J; Posangi, Jimmy; Pinontoan, Odi R (UNIVERSITAS SAM RATULANGI, 2013)
Abstract: The Aedes aegypti mosquitoes are the main vectors of Dengue virus which causes Dengue Fever and Dengue Haemorrhagic Fever. Their blood sucking activity occurs during the day and they rest inside houses (endophagic and anthropophilic). Ae. aegypti females prefer to lay eggs in man-made containers. The purpose of this study was to determine the habitat and development of Ae. aegypti in four types of water (rain water, well water, tap water, and soap water). The method of this study was random group design. The results showed that Ae. aegypti prefered black containers to white containers. Conclusion: The preference of the Ae. aegypti mosquitos in choosing the water media for laying eggs and their development whether in rain water, well water, tap water, or soap water were not significantly different. Keywords: Aedes aegypti, Dengue, types of water. Abstrak: Nyamuk Aedes aegypti merupakan vektor Dengue utama yang mejadi penyebab Demam Dengue dan DBD. Aktivitas mengisap darah terjadi pada siang hari dan nyamuk dewasa cenderung beristirahat di dalam rumah (endofagik dan antropofilik). Ae. aegypti lebih menyukai wadah buatan manusia untuk tempat berkembang biak. Tujuan penelitian ini untuk mengetahui habitat nyamuk Ae. aegypti pada empat jenis air. Metode penelitian yang digunakan yaitu metode rancangan acak kelompok. Hasil penelitian menunjukkan bahwa Ae. aegypti lebih memilih wadah berwarna hitam dari pada wadah berwarna putih. Simpulan: Preferensi nyamuk Ae. aegypti untuk meletakkan telur pada media air hujan, air sumur, air PAM, dan air sabun tidak memperlihatkan perbedaan bermakna. Kata kunci: Aedes aegypti, Dengue, jenis air.